Gramática visual: uma leitura de imagens em material didático de línguas alemã e inglesa - Bühler, Rosilma Diniz Araújo (2010)
This work consists of an investigation on images belonging to the German coursebook Themen aktuell 1 and the English New English File Elementary from the perspective of the Visual Grammar by the theoreticians Günther Kress e Theo van Leeuwen (2006). Based on Michael Halliday s Systemic Functional Linguistics (1994), the Visual Grammar aims at systematising the image-reading process from a theoretical as well as practical point of view. Through its applicable feature, this work aims at increasing visibility of particular sociocultural elements produced by the authors of foreign language coursebooks. In order to achieve this goal, it will take into consideration the constitutive elements of images as well as the property of images in construing meanings.